Laryngeal sarcoidosis: a case-control study - Duchemann, Boris; Lavolé, Armelle; Naccache, Jean-Marc; Nunes, Hilario; Benzakin, Sylvain; Lefevre, Marine; Kambouchner, Marianne; Périé, Sophie; Valeyre, Dominique; Cadranel, Jacques (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Introduction: We undertook a study on a series of laryngeal sarcoidosis (LS), a very rare and often threatening localization to better specify laryngeal manifestations, sarcoidosis clinical expression and long-term follow-up. Methods: This was a retrospective case-control study. All LS patients from two French centers were included and compared to sarcoidosis patients without laryngeal localization with two controls for one patient. Results: Twelve consecutive LS patients were recruited between 1993 and 2011. LS revealed sarcoidosis in eight cases (67%). The most common symptoms were hoarseness (77%), inspiratory dyspnea (38%) and dysphagia (38%). Epidemiological characterisics were not different. Extrapulmonary localizations were significantly more common in LS patients than in controls (92% vs. 54%, p=0.02), particularly lupus pernio (25% vs. 0%, p=0.03) and nasosinusal involvement (83% vs. 4%, p<0.01) while thoracic involvement was less frequent (58% vs 100%, p < 0.01). Treatment rates were higher in the LS group (92% vs. 58%, p=0.04), and treatment duration was longer (median: 81 vs. 13 months, p=0.04), with frequent long-term treatment (67%, N=8/12). Two patients underwent surgery. One patient needed temporary tracheostomy during the course of the disease; Remission rates were lower in LS patients (9% vs. 58% at 2 years p<0.01). Eventually, there was no death nor definitive tracheotomy. Conclusions: LS is a rare condition that is often associated to other loco-regional localizations. LS are often difficult to manage. Survival is good but may require a medico-surgical approach